A loess deposit in the Late Triassic of southern Gondwana, and its significance to global paleoclimate. (January 2018) - Horn, Bruno Ludovico Dihl; Goldberg, Karin; Schultz, Cesar Leandro
Abstract: This work aims to characterize the depositional systems of the Santa Maria Supersequence (Middle to Late Triassic) in the Paraná Basin and discuss their paleoclimatic significance through the use of field, chemical and paleontologic data. Facies analysis led to the identification of two dominant facies associations: dry mudflat and sheet delta. The dry mudflat facies association dominates in the Pinheiros-Chiniquá and Santa Cruz Sequences, and sheetflood delta facies association occurs only in the Candelária Sequence. Loess deposits were recognized in the lowermost sequences. Evidence for loess deposits includes the absence of floodplain feeding channels, thick, structureless siltstone bodies, overwhelming dominance of grain-size mode in 0.0031 mm and age dispersion of dated zircons. Throughout the Santa Maria Supersequence, the chemical index of alteration indicates semi-arid climate, in agreement with global-scale paleoclimatic conditions. However, during the Carnian the abundance of calcrete decreased and the occurrence of aquatic and semi-aquatic fauna increased, implying an increase in humidity in this interval. Other fossiliferous basins in Gondwana recorded the same short-lived, humid event. The humid peak may be associated with the Carnian "Wet Intemezzo", related with the development of the Wrangellian large igneous province (LIP). Graphical abstract: Highlights: Identification of a loess deposit in the Triassic of southern Gondwana. Evolution of the depositional environments in the Triassic of southern Gondwana. Paleoclimate considerations based on the integration of facies analysis and chemical alteration index. Identification of the Mid-Carnian Wet Interval in Brazil.